Analisis Komparatif Tingkat Literasi Keuangan dan Prilaku Pengelolaan Keuangan pada Nasabah Bank Emok dan Bank BRI Unit Tanjung Jaya di Desa Sukaratu Kec.Cilebar Kab. Karawang - Surahman, Surahman; Sihabudin, Sihabudin; Fauji, Robby (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The financial sector, especially banking, is considered a pillar of economic growth and national stability which plays an important role in improving people's living standards by collecting funds from them to support national development. However, limited access to formal financial institutions encourages people to seek loans from non-formal institutions such as Bank Emok. BRI Bank is also an option, but complex administrative procedures and fear of difficult requirements are obstacles. Most people prefer loans from Emok Bank or loan sharks. The majority of the people of Sukaratu Village work as agricultural laborers to meet their living needs, but the people of Sukaratu Village need more money to improve their standard of living, such as business capital and educational needs. Therefore, improving financial literacy and financial management behavior is essential to help people overcome economic problems and improve their standard of living. This research aims to conduct a comparative analysis regarding the level of financial literacy and financial management behavior between customers of Bank Emok and Bank BRI Tanjung Jaya Unit in Sukaratu Village, Cilebar District, Karawang Regency. The data analysis method used is quantitative research and uses a quantitative descriptive research method design: comparative study. The sample used in this research was 69 Bank Emok customers and 65 Bank BRI Tanjung Jaya Unit customers, respondents who had loans at the bank. This research uses sample Independent T Tast Test analysis, which is a statistical test used to test the average difference between two unpaired variables, based on the sample Independent T Tast Test carried out on customers of Bank Emok and Bank BRI Tanjung Jaya Unit, the results of t -test for Equality of Means Sig value. (2-tailed) greater than 0.05. shows that there is no significant difference between the average level of financial literacy and financial management behavior of Bank Emok and Bank BRI Tanjung Jaya Unit customers. Keywords: BRI Bank Tanjung Jaya Unit Customers, Emok Bank Customers, Financial Literacy, Financial Management Behavior.